PEMBERDAYAAN SOSIAL EKONOMI JAMA’AH HAJI INDONESIA - Luthfy Rijalul Fikri (STIT AL-AMIN KREO TANGERANG, 2022)
As the country with the largest population of Muslims in the world, every year Indonesia sends hundreds of thousands of pilgrims to al-Haramain (Mecca and Medina) to perform the Hajj and Umrah pilgrimages. If the implementation of the pilgrimage began to intensify in the 16th century AD, until now, the Indonesian people have sent prospective pilgrims for more than four centuries, and this means that they have sent as many as 400 times, and if each pilgrimage season sends an average of 50,000 people , so currently the number of Indonesian hajj pilgrims has more than 100 million jama'ah. The number of pilgrims who are an extraordinary asset or capital, if empowered to the maximum, can bring progress to the people and nation of Indonesia. The hope of the pilgrims to achieve the title of hajj mabrur is actually not only to give meaning and benefits and blessings to those concerned, but also to give meaning, benefits and blessings to the people, nation, state, and even humanity in general. Likewise, the commitment of the Ministry of Religion of the Republic of Indonesia in organizing pilgrimages that are safe, comfortable, orderly, and in accordance with Islamic law, as well as the determination of the Indonesian Hajj Fraternity Association as stated in its vision and mission, can be realized, it will further strengthen the importance of empowering the potential of pilgrims maximally. The implementation of empowering the pilgrims in order to provide benefits, blessings and kindness to the people, society, nation, state and humanity actually has a functional and substantial relationship with the implementation of the mabruran pilgrimage. By referring to the verses of the Qur'an, al-Hadith, the opinions of prominent Muslim scholars and scholars as well as observations, this paper seeks to analyze the characteristics of the mabrur pilgrimage in relation to the socio-economic empowerment of Indonesian pilgrims in particular, and Indonesian society. in general. This paper will first present a number of reasons for the importance of empowering the people's economy, and end by offering models of strategies for empowering the people's economy based on their strengths, weaknesses, opportunities and threats.